Chemical Quality of Synbiotic Yogurt using Lactobacillus bulgaricus as Probiotics With Mulu Bebe Banana Puree - Talebe, Yusnaini B.; Lestari, Sri (Sangia Research Media and Publishing, 2020)
This study aimed to evaluate the best formulation based on the ratios of Mulu Bebe banana puree on synbiotic yogurt. This study used 10% Lactobacillus bulgaricus lactic acid and mulu bebe banana puree incorporated into liquid milk, with the ratios (banana puree to liquid milk) of 1: 0.25; 1: 0.5; 1: 0.75, and 1: 1. Analysis of synbiotic yogurt focused on chemical properties, including moisture, ash, protein, fat, and carbohydrate. The data analysis was subjected to one-way ANOVA in a Completely Randomized Design (CRD) with 3 (three) replications. The result showed that the synbiotic yogurt using L. bulgaricus probiotics and different volumes of mulu bebe banana prebiotic meet the SNI 2981: 2009 requirements for nonfat yogurt, namely a maximum fat content of 0.5%, a minimum protein of 2.7%, and an optimum ash content of 1, 0%. Regarding quality, the best yogurt in this study contained 10% probiotics and 2.5% mulu bebe banana pure prebiotic.